(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
The purpose of this research is to evaluate the physical, comfort, structural and thermal properties of banana fabrics for their suitable use with cow nubuck and goat nubuck leather in footwear applications. It is observed that all these fabrics have mechanical properties comparable to those of cow nubuck and goat nubuck leather. The tensile strength of the banana fabric is sufficiently higher than that of cow nubuck and goat nubuck leather. Cow nubuck leather, on the other hand, outperforms all other fabrics in terms of percentage elongation. Scanning electron microscopic examination gives solid proof of the banana fabrics’ distinctive fibre pattern in each fibre bundle (yarn) as well as their composition. The banana fabric has greater thermal stability than cow nubuck leather. The results of this investigation indicate that the chosen banana fabrics can be used to create footwear.